The world of Rembrandt, 1606-1669 - Wallace, Robert 1919-; Time-Life Books ([Amsterdam, Nederlands] Time-Life International (Nederland) B.V., 1969)
Lavishly illustrated account of the life, career, works and times of the 17th century Dutch artist Rembrandt van Rijn, with background information on other artists of that period.
The Legend and the Man -- Prelude to Greatness -- Prodigal Years -- Rembrandt's Holland -- An Exploration of Styles -- Triumphs and Trials -- The Last Full Measure.
Includes bibliographical references (p. 183) and index.
Keywords: Rembrandt Harmenszoon van Rijn -- 1606-1669.